Toward a comprehensive understanding of multichannel e-commerce behavior: A systematic literature review - Nadhira, Rizka; Aprilia, Hafiza (Communications in Humanities and Social Sciences, 2025)
This objective of this study is to synthesize studies on consumer usage behavior in multichannel e-commerce through a systematic literature review (SLR). A total of thirteen Scopus-indexed articles published between 2013 and 2025 were analyzed to answer three research questions: (RQ1) how is multichannel usage behavior conceptualized? (RQ2) how are theories used to explain this behavior, and (RQ3) what factors support multichannel e-commerce usage behavior? The review results indicate that multichannel behavior is generally understood as the integrated use of cross-channel technologies, with a theoretical basis dominated by theories of adoption, decision-making, and post-adoption evaluation. For RQ3, focusing on Structural Equation Modeling (SEM)-based studies, satisfaction, perceived value, trust, and perceived usefulness have consistently been demonstrated to influence usage behavior. This review reveals a gap in the use of theory in multichannelsystems dominated by causal explanations at the individual level and provides directions for further research.